Blended learning in teaching English at secondary schools in Sarawak / Magdaline Muuk - Muuk, Magdaline (2012)
The revolutions of technology and Internet have driven the development in education towards applying technology and enhancing Internet in teaching and learning. Educators are taking up the challenges to develop their teaching strategic plans. ESL teachers are having their own ways in applying the principles of teaching to digital learning environments. This paper aims to investigate teachers' why ESL teachers apply blended learning in their lesson. In addition, it also looks into factors of consideration before ESL teachers implement BL and tools used in the BL lesson. Apart from that, the study looks into students' perception towards their blended learning lessons. The study identified characteristics for a BL lesson in ESL, provide suggestions on why applying and using technology into it and provide feedback on students' acceptance levels for the lessons. 27 ESL teachers and 378 students participated in the survey. The data were collected using in-depth interview questions and questionnaire. The findings revealed that ESL teachers applied BL in their lesson using five main tools; video, song, movie, Power Point Presentation and CD/DVD and software provided by the Ministry of Education. The findings also found that students are satisfied with the current BL lesson.